(untitled) (International journal of artificial intelligence, 2025)
The cultures, histories, and languages of two fraternal nations Uzbek and Kazakh who have long lived in Central Asia have always been closely intertwined, contributing to each other’s development. In the Navoi region, Uzbeks and Kazakhs have lived side by side for centuries, and in some areas, they have coexisted in mixed communities. Naturally, this has influenced the language of each ethnic group. This article comprehensively classifies the dialectal characteristics of the language of the Kazakh diaspora in Uzbekistan’s Navoi region.